Does Arterial Hypertension Affect Plasma Levels of Matrix Metalloproteinases and Their Tissue Inhibitors in Patients with Stable Coronary Artery Disease? A Preliminary Study. (4th November 2019) - Kuliczkowski, Wiktor; Banaszkiewicz, Marta; Mysiak, Andrzej; Makaś, Grzegorz; Bil-Lula, Iwona
Abstract : Background . Arterial hypertension (HT) is a serious and prevalent epidemiological factor in the development of coronary artery disease (CAD). Metalloproteinases (MMPs), especially MMP-2 and MMP-9, and their natural endogenous tissue inhibitors (TIMPs) are involved in the pathogenesis of HT and its complications. MMPs are also involved in the development of diabetes (DM), a risk factor for CAD. The aim of the study was to explore the influence of CAD, HT, and DM on changes in plasma levels of MMP-2 and MMP-9 and their inhibitor TIMP-4. Methods and Results . The study involved 70 patients with stable CAD admitted for coronary angiography and 15 healthy subjects. Whole blood samples were collected prior to angiography. MMP-2, MMP-9, and TIMP-4 levels in plasma were estimated using ELISA tests. CAD patients showed a significantly increased level of TIMP-4 and decreased level of MMP-2 in comparison to healthy controls (p = 0.011 and p = 0.037, respectively). Concentration of MMP-2, MMP-9, and TIMP-4 did not differ in the group with and without hypertension. Patients with DM presented higher MMP-2 level than patients without DM (p < 0.001 ). Multiple regression analysis of the influence of independent variables such as CAD stage, DM, and HT on MMP-2, MMP-9, and TIMP-4 showed that only DM was independently associated with a higher level of MMP-2 ( β  = 0.42, R 2  = 0.17, p < 0.001 ). Conclusion . Data showed that patients with CAD presented higher TIMP-4 and lower MMP-2 concentration regardless of HT and DM. HT had no effect on MMP-2, MMP-9, and TIMP-4 levels in serum. DM was independently associated with higher MMP-2 concentration; however, co-occurrence of CAD and DM was associated with the balance in the MMP-2 level. Concentration of MMP-9 did not change significantly in any of the analysed groups.